1998
DOI: 10.1021/jf970659x
|View full text |Cite
|
Sign up to set email alerts
|

Radiotracer Studies on the Formation of 2,5-Dimethyl-4-hydroxy-3(2H)-furanone in Detached Ripening Strawberry Fruits

Abstract: The transformation of 12 radioactively labeled compounds into 2,5-dimethyl-4-hydroxy-3(2H)-furanone (DMHF), glycosidically bound DMHF, and 2,5-dimethyl-4-methoxy-3(2H)-furanone (DMMF) was investigated in detached ripening strawberry fruits (Fragaria × ananassa) over a 3-day period. Radiochemical analysis of the different fruit parts revealed that major portions of the applied radioactivity (up to 66%) remained in the stems and calyx. Incorporation levels of [2-14C]dihydroxyacetone, d-[1-3H]glucose, d-[U-14C]-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 19 publications
4
42
0
Order By: Relevance
“…Naturally occurring HDMF was removed by dialysis (exclusion limit, 10 kD) against a phosphate buffer solution, pH 7.0. Standard activity assays consisted of the dialyzed crude strawberry protein extract, D-fructose-1,6-diphosphate, as HDMF precursor (Roscher et al, 1998) and the reducing agent NADH, because the conversion involves a reduction step. After 24 h of incubation, a solid-phase extraction was performed and the products eluted by diethyl ether were analyzed by HPLC-UV (285 nm), HPLC-diode array detection (DAD), and HPLC-mass spectrometry (MS).…”
Section: Development Of An Assay For the Determination Of Hdmf-forminmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally occurring HDMF was removed by dialysis (exclusion limit, 10 kD) against a phosphate buffer solution, pH 7.0. Standard activity assays consisted of the dialyzed crude strawberry protein extract, D-fructose-1,6-diphosphate, as HDMF precursor (Roscher et al, 1998) and the reducing agent NADH, because the conversion involves a reduction step. After 24 h of incubation, a solid-phase extraction was performed and the products eluted by diethyl ether were analyzed by HPLC-UV (285 nm), HPLC-diode array detection (DAD), and HPLC-mass spectrometry (MS).…”
Section: Development Of An Assay For the Determination Of Hdmf-forminmentioning
confidence: 99%
“…The first indications for the enzymatic formation of HDMF in strawberry fruit were provided by studies demonstrating the correlation of fruit ripening stage and HDMF concentration (Sanz et al, 1995). Incorporation experiments showed that, after the application of 15 different water-soluble, radioactively labeled substances, D-[U-14 C]fructose-1,6-diphosphate had the highest incorporation rate into the furanone structures (Roscher et al, 1998) (Schwab, 1998), and studies with D-[2-2 H]glucose demonstrated the involvement of phosphohexose isomerase in the conversion of D-glucose to the furanones, thus confirming the proposal that D-fructose-6-phosphate is a natural precursor of HDMF and DMMF (Wein et al, 2001). Even though the detailed biogenetic pathway from D-fructose-1,6-diphosphate to HDMF remained unknown, all studies have indicated that HDMF is derived from carbohydrate metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…d -Glucose, d -fructose, d -fructose 6-phosphate, and d -fructose 1,6-diphosphate have been confirmed as intermediates of the precursor pathway of DMHF formation in strawberries. 4749 It has further been shown that in ripening strawberries, DMHF is a methylation substrate, and S -methyl- 14 C-adenosyl- l -methionine is the methyl donor in the biosynthesis of mesifurane (DMMF). 50 The locus required for the production of mesifurane in strawberry is the Fragaria x ananassa O -methyltransferase gene ( FaOMT ), and the partially purified enzyme has a molar mass of 80 kDa.…”
Section: Biosynthesis and Properties Of Mesifuranementioning
confidence: 99%
“…D-Xylulose-5-phosphate, D-ribulose-5-phosphate, and D-sedoheptulose-7-phosphate were determined as potential precursors of homofuraneol and norfuraneol (31). Hecquet et al (13) demonstrated that HDMF is produced by Z. rouxii from D-fructose-1,6-bisphosphate (FBP), and results from Roscher et al (30) confirmed FBP as the most effective precursor in ripe strawberry fruits. Z. rouxii produced approximately 80 ppm of HDMF after 11 days of incubation in nutrient solutions containing 10% FBP and 5% D-glucose (carbon source).…”
Section: -Hydroxy-3[2h]mentioning
confidence: 99%